Screening for Occult Cancer in Patients with Venous Thromboembolism: Past, Present, and Future - van Es, Nick; Ay, Cihan; Jara-Palomares, Luis (Hämostaseologie, 2020)
A strong link between cancer and thrombosis has been well recognized. The occurrence of venous thromboembolism (VTE) can be the first clinical sign of an undiagnosed (i.e., occult) cancer. Cancer is more often diagnosed after unprovoked compared with provoked VTE events, with a reported risk in recent studies of around 5%. Extensive, imaging-based screening strategies to detect occult cancer after unprovoked VTE do not appear to have a clear clinical benefit compared with a more limited cancer screening. To identify patients with unprovoked VTE at high risk of occult cancer, risk factors have been explored and prediction models developed. Relevant risk factors for occult cancer include male sex, age, anemia, chronic lung disease, and thrombocytosis. Studies with preselection of patients based on risk assessment and evaluation of limited versus extensive screening strategies are currently ongoing. Also, novel and promising approaches for early detection of cancer in patients with unprovoked VTE by means of liquid biopsies, which include analysis of circulating tumor cells, cell-free tumor DNA, proteomics, or platelet mRNA sequencing, are currently under investigation. In this review, we provide an overview of the risk of cancer diagnosis after VTE, discuss the studies which investigated different screening strategies for occult cancer, summarize risk factors and risk scoring models for identification of patients at high risk of cancer diagnosis after VTE, and highlight ongoing research to optimize screening and identification of patients at risk of occult cancer, which will shape the future clinical practice.
Keywords: cancer; venous thromboembolism; thrombosis